2000
DOI: 10.1021/la9911584
|View full text |Cite
|
Sign up to set email alerts
|

Control of Surface and ζ Potentials on Nanoporous TiO2 Films by Potential-Determining and Specifically Adsorbed Ions

Abstract: The effect of a specifically adsorbed ion, phosphate, on the electrochemical response and adsorption properties of nanocrystalline TiO2 is examined. Phosphate is known to affect the ζ potential, as measured by electrophoretic mobility, by changing the charge of the oxide surface. The adsorption of a cationic probe molecule, thionine, onto TiO2 was monitored with an in-situ cell using UV−vis spectroscopy. The adsorption of the cationic dye molecule was found to be governed by changes in the ζ potential, whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
77
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 47 publications
11
77
2
Order By: Relevance
“…Actually, the defect structure of TNTs formed by oxygen vacancies favors the adsorption of water on the surface and then dissociates water into hydroxyl groups and protons [61][62][63]. This dissociation behavior leads to the charged surface of TNTs due to the loss or gain of protons and complexation reactions of surface hydroxyl groups [64,65] Electrophoretic mobility is the most common technique for investigating the surface charges of the metal oxide/electrolyte solutions [66,67]. …”
Section: Surface Hydroxyl Groups and Surface Chargesmentioning
confidence: 99%
“…Actually, the defect structure of TNTs formed by oxygen vacancies favors the adsorption of water on the surface and then dissociates water into hydroxyl groups and protons [61][62][63]. This dissociation behavior leads to the charged surface of TNTs due to the loss or gain of protons and complexation reactions of surface hydroxyl groups [64,65] Electrophoretic mobility is the most common technique for investigating the surface charges of the metal oxide/electrolyte solutions [66,67]. …”
Section: Surface Hydroxyl Groups and Surface Chargesmentioning
confidence: 99%
“…The isoelectric point of titania is reported to be around 5. 12,13 Since the pKa of phosphinate group of D,L-GLUF is 2.37, 14 phosphinate can be bonded to cationic Ti at the titania surface at the acidic region, as reported for the phosphate anion. 15 The adsorption of D,L-GLUF decreased with increase in pH beyond pH 3.…”
Section: Pre-separation Of Dl-gluf With Titaniamentioning
confidence: 85%
“…It has been already reported that the point of zero zeta potential of the nano titania particles are shifted to lower pH value in the presence of phosphate anion which indicates the accumulation of negative charges on the surface of nano titania. 37 It seems, a negative electrostatic field could be formed in the surface layer of the nano titania due to the existence of negatively charged phosphate anions. During the photocatalysis process, the separation of electrons and holes could be promoted by this negative electrostatic field and as a result the charge recombination on phosphate modified nano titania is suppressed compared with the pure nano titania.…”
Section: The Effect Of Surface Modification With Phosphate On Photocamentioning
confidence: 99%